Risk factors of recurrence after drug withdrawal in children with epilepsy - Zhao, Yongheng; Ding, Hao; Zhao, Xiaoyu; Qiu, Xiaochang; Li, Baomin (Frontiers in Neurology, 2023)
This study aimed to evaluate the risk factors for recurrence in pediatric patients with epilepsy following normal antiseizure medication (ASM) treatment and drug withdrawal. We retrospectively analyzed 80 pediatric patients who received treatment at the Qilu Hospital of Shandong University between January 2009 and December 2019 after at least 2 years of seizure-free and normal electroencephalography (EEG) before the regular drug reduction. Patients were followed-up for at least 2 years and divided into the recurrence and nonrecurrence groups based on whether relapse occurred. Clinical information was gathered, and the risk variables for recurrence were statistically analyzed. Post 2 years of drug withdrawal, 19 patients showed relapses. The recurrence rate was 23.75%, and the mean time of recurrence was 11.09 ± 7.57 months, where 7 (36.8%) were women and 12 (63.2%) were men. In all, 41 pediatric patients were followed-up until the 3rd year, of which 2 (4.9%) patients experienced a relapse. Among the remaining 39 patients without relapse, 24 were followed-up until the 4th year, and no recurrence occurred. After being monitored for >4 years, 13 patients experienced no recurrence. The differences in the history of febrile seizures, combined use of ≥2 ASMs, and EEG abnormalities after drug withdrawal between the two groups were statistically significant (p < 0.05). Multivariate binary logistic regression analysis revealed that these factors are independent risk factors for recurrence after drug withdrawal in children with epilepsy: history of febrile seizures (OR = 4.322, 95% CI: 1.262–14.804), combined ASM use (OR = 4.783, 95% CI: 1.409–16.238), and EEG abnormalities after drug withdrawal (OR = 4.688, 95% CI: 1.154–19.050). In summary, our results suggest that the probability of seizure recurrence following drug cessation may be greatly increased by a history of febrile seizures, concomitant use of ≥2 ASMs, and EEG abnormalities after drug cessation. The majority of recurrences occurred in the first 2 years following drug discontinuation, whereas the rate of recurrence was minimal thereafter.